IMPLEMENTATION OF A DATA SECURITY SYSTEM USING ENCRYPTION METHODS ON WEB-BASED DATA - Galih Kurniawan Sidik; Wahyudin (JURNAL ILMIAH EDUNOMIKA, 2026)
Data security in web-based ecosystems has become a crucial issue with the increasing cyber threats and society's dependence on digital platforms. This study explores the implementation of data security systems using various encryption methods, including Advanced Encryption Standard (AES) and Rivest-Shamir-Adleman (RSA), to protect the integrity and confidentiality of information in web applications. The main issue raised is the vulnerability of data during transmission and storage on cloud servers, which are often targets of Man-in-the-Middle (MitM) attacks and database leaks. The methodology used is a software development life cycle (SDLC)-based system development with a focus on the integration of encryption layers in databases and HTTPS communication channels. The results show that the implementation of end-to-end encryption significantly reduces the risk of unauthorized access without excessively compromising system latency. In conclusion, the combination of symmetric and asymmetric encryption provides layered protection that is essential in maintaining user trust and compliance with global data protection regulations.